IMPACT OF MUSICAL APPEAL IN ADVERTISEMENT ON CONSUMER MINDSET - Patil, Kunal; Tilak, Geetali; Pawar, Priyanka (ShodhKosh: Journal of Visual and Performing Arts, 2024)
This research investigates the profound impact of musical appeal in advertising on consumer perception and purchase behavior. Through a quantitative study involving 328 respondents, the study examines the influence of music in advertisements on brand perception and consumer purchasing decisions. The findings reveal a strong correlation between the presence of music in ads and enhanced brand perception, including brand image, credibility, and overall appeal. Moreover, the study underscores the significant influence of musical elements on consumers’ inclination toward considering and making purchases related to advertised brands. The results suggest that strategically incorporating music in advertisements holds substantial potential to shape consumer perceptions and drive purchase behavior, emphasizing its role as a powerful tool in contemporary advertising strategies.